Relationship between enteral nutrition timing and 28-day mortality in critically ill stroke patients in the MIMIC-IV database - Wang, Xiaoliang; Xie, Xiuling; Xu, Xin; Tan, Lan (Frontiers in Neurology, 2024)
The ideal timing for commencing enteral nutrition (EN) in critically ill stroke patients within the intensive care unit (ICU) remains a subject of debate, with ongoing controversy regarding the influence of early EN initiation. Here, we investigated the association between the timing of EN initiation and 28-days mortality using data from the MIMIC-IV database.Methods: Employing a retrospective cohort design, this study harnessed the MIMIC-IV database to identify stroke patients who received EN during their hospital stay.The main focus of this investigation was to examine 28-days mortality following the hospital admission . The analysis accounted for various demographic, clinical, laboratory, and intervention variables as covariates. COX regression analysis was employed to assess the correlation between the timing of EN initiation and 28-days mortality and RCS (Restricted Cubic Splines) analysis was used to test for nonlinear correlation. Patients were then stratified into 2 cohorts depending on the timing of EN initiation: EN initiation within 2 days (n=564) . EN initiation beyond 2 days(n=433) . Multi-variates COX regression was used to investigate the difference of 28-days mortality between groups.Results: In total, 997 participants were included in the study, with 318 (31.9%) died in 28 days. We observed that the timing of EN initiation was correlated with 28 days mortality but the correlation was not significant after adjusted by covariates (crude HR: 0.94, 95%CI: 0.88 1, p=0.044; adjusted HR:0.96, 95%CI:0.9 1.02, p=0.178).RCS showed that the correlation was not in a nonlinear fashion.Strikingly, compared with the late EN initiation group in the multivariate regression models, a higher mortality rate exhibited in the early EN (OR=1.34, 95% CI: 1.06 1.67, p=0.012). After adjusting for various confounding factors in the multi-variable COX models, we identified that patients in the early EN group had a 28% higher risk of mortality than those in the reference group (OR=1.27, 95% CI:1 1.61, p=0.048). These associations remained consistent across various patient characteristics, as revealed through stratified analyses.The early commencement of EN in ill stroke patients may be linked to a heightened risk of higher 28 days mortality, indicating the need for further investigation and a more nuanced consideration of the optimal timing for commencing EN.